2015
DOI: 10.3389/fmicb.2015.00337
|View full text |Cite
|
Sign up to set email alerts
|

Forest floor community metatranscriptomes identify fungal and bacterial responses to N deposition in two maple forests

Abstract: Anthropogenic N deposition alters patterns of C and N cycling in temperate forests, where forest floor litter decomposition is a key process mediated by a diverse community of bacteria and fungi. To track forest floor decomposer activity we generated metatranscriptomes that simultaneously surveyed the actively expressed bacterial and eukaryote genes in the forest floor, to compare the impact of N deposition on the decomposers in two natural maple forests in Michigan, USA, where replicate field plots had been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 61 publications
5
51
2
Order By: Relevance
“…To compare patterns from the ribosomal survey and a functional gene, we utilized existing metatranscriptome data generated from the same samples used in the current study [18]. We compared the proportion active OTUs using rRNA to rDNA ratios to the relative abundance of a gene associated with transitions from dormant to active states, the resuscitation promoting factor C (rpfC), which has been found in numerous metagenomes and is prevalent in soils [3].…”
Section: Resuscitation Promoting Factor Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To compare patterns from the ribosomal survey and a functional gene, we utilized existing metatranscriptome data generated from the same samples used in the current study [18]. We compared the proportion active OTUs using rRNA to rDNA ratios to the relative abundance of a gene associated with transitions from dormant to active states, the resuscitation promoting factor C (rpfC), which has been found in numerous metagenomes and is prevalent in soils [3].…”
Section: Resuscitation Promoting Factor Analysismentioning
confidence: 99%
“…We compared the proportion active OTUs using rRNA to rDNA ratios to the relative abundance of a gene associated with transitions from dormant to active states, the resuscitation promoting factor C (rpfC), which has been found in numerous metagenomes and is prevalent in soils [3]. Methods for preparation of samples for sequencing on the Illumina HiSeq 2000 can be found in Hesse et al (2015) [18]. Of the 12 samples from the ambient plots, three failed to produce libraries, reducing the number of matched ribosomal-transcriptome samples to 7.…”
Section: Resuscitation Promoting Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Among soil microorganisms, saprotrophic fungi are considered to be the most efficient decomposers of these biopolymers due to their important lignocellulolytic potential, filamentous growth form and wide diversity in soils Talbot et al, 2015). Indeed, despite the presence of diversified bacterial communities in forest litters and soils (Urbanov a et al, 2015), fungal lignocellulolytic transcripts are more abundant in soils (Hesse et al, 2015) and a study using a metaproteomic approach reported that all hydrolytic enzymes identified from beech litter extracts were likely produced by saprotrophic fungi (Schneider et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the assemblage of the active fungal communities was assessed by the sequencing of a fragment of the Elongation Factor 1-alpha (EF1a) gene, a housekeeping and constitutively expressed eukaryotic gene (Rehner and Buckley, 2005). Indeed, neither the intron-like rDNA internal transcribed spacer (ITS) region nor the nuclear large and small-subunit rDNA encoding genes (28S and 18S), widely used as barcode markers for fungal identification in environmental studies (Schmidt et al, 2013;Hesse et al, 2015), can be amplified from environmental cDNAs synthesized from eukaryotic poly-A mRNA using oligo(dT) primers. Although the EF1a gene sequence has a poor species-level resolution in fungi compared to the ITS (Schoch et al, 2012), EF1a sequence assignation to the main fungal phyla or sub-phyla can be confidently performed (Roger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%